Sejarah Dakwah di Tengah Pluralisme Agama Pondok Pesantren Dar Al-Tauhid Arjawinangun - Fifi Novianty (IAIN Syekh Nurjati Cirebon, 2021)
Dakwah in the midst of religious pluralism brought by K.H. A. Syatori at Dar Al-Tauhid Arjawinangun Cirebon Islamic Boarding School had a positive impact. Social relations between students and the community around both Muslims and non-Muslims into harmony. K.H. A. Syatori in applying the learning method in the cottage is also very well known. In the education system applied in the Dar Al-Tauhid Islamic Boarding School the salafi system was for two, namely the Sorogan and Bandongan models as well as class-class or madrasah classical models with special levels and those that have been determined. In addition to focusing heavily on the process of learning the Qur'an, K.H. A. Syatori also always informs students of the Dar Al-Tauhid Islamic Boarding School to be interconnected among religious communities, while the religious environment of the students diverts this inseparable from this the influence of education applied by K.H. A. Syatori Dar Al-Tauhid Islamic boarding school is the first cottage in Arjawinangun Regency. Cirebon, and one of the places to spread Islamization in Cirebon. The figure who became the pioneer of Islamization in the midst of religious pluralism in Islamic Boarding School, namely K.H. A. Syatori has proven to his people that Islam is a religion that will increase the level of understanding and can unite with other non-Muslims so as to create a beautiful religious harmony in the environment of Dar Al-Tauhid Arjawinangun Islamic Boarding SchoolKeywords: Religion, Dakwah, Pluralism, History